Studi eksperimental pengaruh mapping waktu pengapian dan mapping durasi injeksi serta rasio kompresi terhadap perrformansi dan emisi gas buang engine honda CB150R berbahan bakar E50 - Dwijo Hartono; Marthen Paloboran; Bambang Sudarmanta (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
Bioethanol is a vegetable fuel that is formulated for motor vehicles. In the application of bioethanol in combustion engines, it requires some modifications to the engine to be used such as changing the ignition time, changing the duration of the injection, changing the compression ratio, and modifying the engine fuel input system. Thus, it is expected to increase the performance of the engine performance. This study focused on Honda CB150R engine with the initial setting on the ECU programmable. Thereafter the fuel injection testing to achieve AFR Bioethanol E50 with injection percentage of 100, 125, 150, 175 and 200 percent of the total fuel injection standard. Then tested using Pertamax (0% bioethanol) under standard conditions as the control group and the use of Bioethanol E50 with variation of ignition timing as the test group by taking 4 variations of advance ignition timing 16 °, 20 °, 24 ° and 28 ° BTDC at compression ratio which has been converted to 12, 12.5, and 13. From this research, the exact mapping of injection mapping at 2000 to 4000 rpm is 150%, while at 5000 to 8000 rpm, the best duration is 125%. As for the ignition timing mapping is obtained in the range of 16 ° and 20 ° BTDC for the compression ratio of 12, 12.5, and 13. Based on the results of au Eu ecu programable on the compression ratio 11 obtained an average value of 13.154 which means the condition of air and material mixture burn is under the afr stoichiometry ie 14.7. As for the results of afr E50 ecu programable on the compression ratio 11 obtained an average value of 11.160, which means the condition of air and fuel mixture is under the afr stoikiometri is 12.6. It shows that the Honda CB150R engine operates on afr under the stoichiometry of the fuel used. So Honda CB150R engine has the characteristics of power to be increased and no detonation occurs, but the fuel consumption time value will decrease as well as CO and HC emissions increased